REFLECTION OF MORAL AND ETHICAL PROBLEMS IN THE PROSE OF L. BOZIEV - TIMIZHEV, Kh.T.; BOZIEVA, N.B. (Kavkazologiya, 2021)
The article presents an attempt to analyze the moral and ethical problems of modern society in the prose of Lyudin Boziev. The writer performed mainly in the genre of lyrical prose, so his "I" plays a significant role in his work. It also draws attention to the autobiography of his works, in which he reflected the feelings and thoughts of his generation – the "children of war"; the movement of time and the complexity of human relationships. The authors of the article connect the moral search of L. Boziev with the national character, which is changing intensively in the era of globalization. The relevance of the research topic is determined by its innovative nature, associated with the analysis of the unexplored works of the Kabardian prose writer. The purpose of the study is to identify the specifics of the artistic solution of moral and ethical problems in modern Kabardian prose based on the material of L. Boziev's novels "The Arrogant becomes Mean" and "The Road of Life". It is achieved by solving a set of tasks, including: the definition of the national and ethical origins of the concept of "morality", the study of the problems and poetics of the novels of L. Boziev, establishing their connection with the Adyghe mentality, identifying the problem of morality and the specifics of its artistic solution. The research involves a number of general scientific methods (generalization, analysis, synthesis, description). The results obtained can become a theoretical aid in the further study of the work of L. Boziev, as well as in determining the role of a bright creative personality in the evolution of artistic consciousness.